La responsabilidad de cuidar el buen estado de las vías urbanas de Roma y de municipios y colonias - de Castro-Camero, Rosario (Tesserae iuris, 2023)
The adequate development of civic life in Rome and in municipalities and colonies made it essential that streets be in good condition and use. Over time, different people were responsable for their control, as well as for the material performance of necessary tasks. Legal and epigraphic sources provides us with interesting information about its organization and function. A comparative study of them has been the basis for the elaboration of this research work.